IMPROVEMENT OF ECONOMIC MANAGEMENT MECHANISMS TO ACCORDING THE ACTIVITIES OF AGROBUSINESS ENTITIES TO MARKET REQUIREMENTS - Abdurashidova Omadoy Numonjon kizi (International Journal of Innovations in Engineering Research and Technology, 2021)
This article discusses the main mechanisms for adapting agribusiness to a market economy. In addition, special emphasis was placed on the role of agro-business in the economy of Uzbekistan and the ongoing reforms in this area.